Audit of Regional Management Information Systems in Government Institutions - Rifaldi Herikson; Geraldi Catur Pamuji (Peneliti.net, 2020)
Sistem Informasi Manajemen Daerah (SIMDA) is a system that was developed to assist accountability achievement in local government. The aim of this study is to audit the application area management performance information system implemented by government agencies in Tanjungpinang, Kepri. Descriptive approach was used to present an outline of the assets inventory in SIMDA. Data collection methods consist of primary data obtained from interviews and observations. As for secondary data, we used literature studies to support this study. The audit process was used the OCTAVE Allegro approach to analysis important assets owned by the government and manage risk to achieve the ISO 27001 standard. In addition, this research used five of eight steps on OCTAVE Allegro to establish the areas of concern in SIMDA application. The results presented an indication of the data discrepancy between the project proposed data and project data in SIMDA. Lack of user attention in SIMDA checking data before adding or deleting the data caused that indication. The conclusion is by determining areas of concern, it can be used as a mapping of risk to information assets while minimizing the risk as a measure to maintain the information security system of SIMDA. This study was conducted to discuss information security, SIMDA, OCTAVE Allegro, and ISO 27001.